Redefining Pastoral and Gender in J. M. Coetzee's Disgrace - Upadhyay, Toya; Sharma, Kamal (International Journal of Language and Literary Studies, 2025)
The racial and sexist dynamics of the apartheid system in South Africa resonated widely even after its formal end by the 1994 election. Resentment at being brutally mistreated by the whites continued among the black citizens whereas fear of black retribution hunted the white citizens. Social ills inclusive of injustice, robbery, rap, violence, vandalism and so on remained rampant across the country obstructing transition to peace. James Maxwell Coetzee’s novel, Disgrace (1999) encapsulates the troubled Post-apartheid South African context. This paper analyzes Disgrace to examine how it problematizes that condition and depicts a transformative way ahead. Drawing on ecofeminism in align with the concept of pastoral, the paper focuses its analysis on the role of the central character David Lurie and finally comes to a conclusion that he ultimately accepts the sociopolitical transformation despite his initial reluctance. Lurie, a white professor, initially perpetuates apartheidism through sexual violence against many black women including his own student, Melanie Isaacs. However, his perspective gradually changes through the interactions with his daughter after his disgraceful exile to the countryside. His seduction of women, reluctance to admit his wrongdoing, aggression towards the black boys, and unwillingness to shift land ownership authority to Petrus (a black man) reveal his racist, sexist and androcentric ideologies. Contrarily, his repentance to Isaacs’s family, realization of his daughter’s mature outlook towards the blacks and pregnancy, and service to animals prove his transformation into a practitioner of stewardship with biophilic and ecofeminist sensibilities. Additionally, psychological transformation that helps redefine pastoral and woman. Reading the novel from this perspective will contribute to the understanding of the novel’s call for the exigency of transformation in Post-apartheid Africa.